2006
DOI: 10.1097/01.tp.0000234815.23630.4a
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Early Kidney Allograft Dysfunction by Blood Oxygen Level-Dependent Magnetic Resonance Imaging

Abstract: BOLD-MRI demonstrated significant changes in medullary oxygen bioavailability in allografts with biopsy-proven ATN and acute rejection, suggesting that there may be a role for this noninvasive tool to evaluate kidney function early after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
5
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 23 publications
4
62
5
1
Order By: Relevance
“…Nevertheless, other studies using blood oxygen level-dependent magnetic resonance imaging (19) are consistent with the hypothesis of Rosenberger and colleagues that HIF-1␣ expression in rejected kidneys reflects hypoxia in the kidney.…”
supporting
confidence: 73%
“…Nevertheless, other studies using blood oxygen level-dependent magnetic resonance imaging (19) are consistent with the hypothesis of Rosenberger and colleagues that HIF-1␣ expression in rejected kidneys reflects hypoxia in the kidney.…”
supporting
confidence: 73%
“…Evolution of BOLD MRI into a more reliable and reproducible indicator of renal oxygenation is required before this technique can realize its full potential to contribute to our Cortex A Djamali et al 64 Park et al 79 Sadowski et al 65 Sadowski et al 66 Han et al 67 Xiao et al 75 offers great promise in addressing analytic and technical issues that currently limit the ability of BOLD MRI to address intracompartmental heterogeneity in oxygenation, while the work of Zhang et al 5 offers great promise in enhancing the ability of BOLD MRI signal strength to reflect intrarenal pO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Sadowski and coworkers reported BOLD MRI measurements in kidney allografts with ATN (n=4-6) within 4 months post-transplantation. [64][65][66] There was no significant difference in cortical oxygenation in the ATN group compared with normal functioning allografts, although one study showed a trend toward cortical hypoxia. Medullary oxygenation was significantly increased in the ATN group in one study, but not in the other two.…”
Section: Acute Tubular Necrosismentioning
confidence: 93%
See 1 more Smart Citation
“…Blood oxygen level-dependent (BOLD) MRI has been shown to be of potential clinical value in transplanted kidneys [8] and may be helpful for evaluation and separation of kidney allograft dysfunction like ATN or acute rejection [22,23]. Previously we have shown that the relaxation rate from BOLD MRI and F P from DW-MRI provide complementary information [8].…”
Section: Discussionmentioning
confidence: 99%